Diversity of Sergestid Shrimp Acetes (Order Decapoda) in Selected Sites of Sarawak Coastal Water and Its Autecology - Muhammad Nur Arif, Othman (Universiti Malaysia Sarawak, 2022)
Sergestid shrimps Acetes, locally known as ‘bubok’ in Sarawak is a valuable marine resource that supports the livelihood of the coastal communities, particularly during the blooming season (March –April). The shrimps play a significant role in transporting primary producers and consumers energy to higher trophic levels. Sergestid shrimp fishery in Sarawak depends heavily on traditional knowledge and practices, halting the sustainable utilization of this valuable resource. Therefore, the objectives of this study are to determine the diversity of Acetes living along the coastal water of Sarawak (Miri, Lundu, Telaga Air) based on morphological assessment and cytochrome oxidase subunit 1 (CO1) gene analysis and to analyse the interactions between the abundance of Acetes with selected environmental parameters namely dissolved oxygen (DO), temperature, turbidity, pH, salinity, total suspended solid (TSS) and chlorophyll a (chl a) as well as the presence of zooplankton (diet of Acetes) in coastal water of Miri, Sarawak.